Dutch Augustinians, appropriations of Augustine, and ressourcement in the nineteenth and twentieth centuries - Heffernan, Brian (Trajecta, 2017)
Together with such concepts as aggiornamento, ‘reading the signs of the times; and the 'universal call to holiness! ressourcement was one of the cornerstones of the Second Vatican Council's (1962-1965) reform project. For religious institutes in particular, it became a leading principle in their postconciliar attempts to return to the 'charism of their founder; Reform-minded intellectuals proposed ressourcement as a way of remedying the problems that they believed beset the religious life of their time, by making a clean break with rigid and formalistic accretions accumulated over the centuries in order to return to the institutes' authentic, original inspiration. Ressourcement was thus conceived as a way of making new beginnings by effecting a rupture with the recent past. This article takes the Dutch Augustinians as a case study and looks specifically at their various appropriations of the order's primary founder figure, Augustine of Hippo. The example of the Dutch Augustinians illustrates the fact that the call for ressourcement, far from being a conciliar invention, was in fact the product of the pre-conciliar Catholicism that reformers were so keen to repudiate. In the 1930s, it had inspired Dutch Augustinian endeavours to create a militant, virile ethos. For the generation of friars who came of age during the council, ressourcement was associated with reactionary efforts to stifle ‘real; radical reform, and little attention was paid to it in the Dutch province during the 1960s and 1970s. It was not until the 1980s that a new interest in Augustine as the author of a particular school of spirituality emerged and managed to gain support from both the province's progressive and its traditionalist wings. This article thus charts the history of Dutch Augustinian appropriations of Augustine. In doing so it contends that students of ressourcement as a driver of change in the history of religious institutes should divest themselves of the paradigm of ‘good' rupture and 'bad' continuity. This paradigm, produced and promoted by the reformists of the conciliar era, has also found its way into much subsequent historical analysis. In fact, however, it obscures the complexities of the actual uses of ressourcement by various historical agents. Attempts to make historical sense of the conciliar reforms should instead pay close attention to the specific meaning that specific groups assigned to them at any given time.